NILAI KERUGIAN EKONOMI LINGKUNGAN YANG DISEBABKAN OLEH KEBARAKAN HUTAN DAN LAHAN DI PROVINSI RIAU - Annisa Fitria Zerni; B Isyandi; Hendro Ekwarso (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2023)
Forest and land fires in Riau province generally occur due to natural and human factors. Forest and land fires that occurred in Riau province in 2017 covering an area of 6,865 ha, 2018 covering an area of 37,235 ha, 2019 covering an area of 90,551 ha, 2020 covering an area of 15,443 ha while in 2021 covering an area of 8,970 ha can certainly threaten the natural environment. The impact of forest and land fires on the environment. The environmental impact is that it can eliminate biodiversity, release carbon, nutrients and regulate water management. This study aims to determine the value of environmental economic losses from forest and land fires using verification research by processing data on forest and land fires. The data analysis technique uses the Total Economic Value (TEV) approach with the variables used namely the value of damage to biodiversity, the value of carbon release, the value of nutrient loss, and the value of water management. The type of data used is secondary data in the form of a time series between 2017-2021. The results of this study indicate that the total value of environmental economic losses caused by forest and land fires in Riau province in 2017 was Rp 62,712,736,100, in 2018 it was Rp 354,662,779,240, in 2019 it was Rp 859,825,254,756, in 2020 it was Rp 144,299,160,355 and in 2021 it will be Rp 89,198,360,689. Forest and land fires in Riau province threaten biodiversity, cause global warming and increase the potential for disasters. Keyword: Environmental economics, Forest and land fires, economic value, Riau province.